Protocol for the PRIMARY clinical trial, a prospective, multicentre, cross‐sectional study of the additive diagnostic value of gallium‐68 prostate‐specific membrane antigen positron‐emission tomography/computed tomography to multiparametric magnetic resonance imaging in the diagnostic setting for men being investigated for prostate cancer. (12th February 2020) - Amin, Amer; Blazevski, Alexandar; Thompson, James; Scheltema, Matthijs J.; Hofman, Michael S.; Murphy, Declan; Lawrentschuk, Nathan; Sathianathen, Niranjan; Kapoor, Jada; Woo, Henry H.; Chalasani, Venu; Rasiah, Krishan; et al.
Abstract : Objectives: Primary objectives: To determine the additive value of gallium‐68 prostate‐specific membrane antigen (PSMA) positron emission topography (PET)/computed tomography (CT) when combined with multiparametric magnetic resonance imaging (mpMRI) detecting clinically significant prostate cancer (csPCa) in men undergoing initial biopsy for suspicion of PCa, and to determine the proportion of men who could have avoided prostate biopsy with positive mpMRI (PI‐RADS ≥3) but negative PSMA‐PET/CT. Secondary objectives: To determine the proportion of men who had csPCa detected only by PSMA‐PET/CT or only by systematic prostate biopsy; to compare index lesions by template biopsies vs targeted lesions identified on mpMRI or PSMA‐PET/CT; to assess whether there may be health economic benefit or harm if PSMA‐PET/CT is incorporated into the diagnostic algorithm; and to develop a nomogram which combines clinical, imaging and biomarker data to predict the likelihood of csPCa. Patients and Methods: The PRIMARY trial is a multicentre, prospective, cross‐sectional study that meets the criteria for level 1 evidence in diagnostic test evaluation. PRIMARY will investigate if a limited (pelvic‐only) PSMA‐PET/CT in combination with routine mpMRI can reliably discriminate men with csPCa from those without csPCa. We conducted a power calculation based on pilot data and will recruit up to 600 men who will undergo PSMA‐PET/CT (the index test), mpMRI (standard test) and transperineal template + targeted (PSMA‐PET/CT and/or mpMRI) biopsies (reference test). The conduct and reporting of the mpMRI and PSMA‐PET/CT will be blinded to each other. Results: The PRIMARY trial will measure and compare sensitivity, specificity, positive predictive value and negative predictive value of both mpMRI and PSMA‐PET/CT vs targeted prostrate biopsy. The results will be used to determine the proportion of men who could safely avoid biopsy without compromising detection of csPCa. Furthermore, we will assess whether there is a health economic benefit in incorporating PSMA‐PET/CT into the diagnostic algorithm. Conclusions: This trial will provide robust prospective data to determine the diagnostic ability of PSMA‐PET/CT used in addition to mpMRI. It will establish if certain patients can avoid biopsy in the investigation of PCa.